Performance of U(Ⅵ) enrichment by tannic acid sodium and alginate composite microspheres - LIU Qing; HUANG Jianbin; LI Weifan; ZHAO Guodong; YANG Jingjing (Gongye shui chuli)
With the rapid development of nuclear energy, the development of environmentally friendly bio-based adsorbents is of great significance for controlling radioactive nuclide pollution. A novel tannic acid and sodium alginate (TA/SA) composite microsphere was prepared using a mixed crosslinking method. The effects of TA/SA mass ratio, solution pH, initial concentration of U(Ⅵ), contact time, and temperature on the adsorption behavior of U(Ⅵ) by TA/SA microspheres were investigated, and the adsorption kinetics and thermodynamics were studied. The adsorption mechanism of TA/SA microspheres on U (Ⅵ) was also explored. The results showed that the optimal mass ratio of TA to SA was 1∶2, and pH had little effect on the adsorption of U(Ⅵ) by TA/SA microspheres. When the mass concentration of U(Ⅵ) was 50 mg/L, the dosage of TA/SA microspheres was 0.1 g/L, the solution pH was 4, the temperature was 323 K, and the contact time was 2 hours, the maximum adsorption capacity of TA/SA microspheres for U(Ⅵ) was 263.42 mg/g. The adsorption behavior conformed to the quasi second order kinetic model and Freundlich isotherm adsorption model. The adsorption of U(Ⅵ) by TA/SA microspheres was a spontaneous endothermic process, and the reaction could be divided into three stages, including surface adsorption, mesopore diffusion, and micropore diffusion. TA/SA microspheres had an irregular grooved surface and a three-dimensional network structure with numerous openings inside. The reduction reaction played a dominant role in the adsorption of U (Ⅵ) by TA/SA microspheres.